THE IMPLEMENTATION OF ONLINE NEWSPAPER IN TEACHING READING - Yuliarsih Yuliarsih; Sri Harini (The Ellite of Unira, 2023)
This study was conducted at SMP Plus Al Madaniyah. The participants of this study were seventh grade students of SMP Plus Al Madaniyah..The data were obtained through classroom observation and interview. It was found that through the activity, the students not only using the language, but also reading the language and speaking with the language.The last, the final observation. It was found that the students were able to rewrite the news with their own words.The last, the final observation. It was found that the students were able to rewrite the news with their own words. The lessons observed were reading lessons. The result of interview found some benefits from the use of online newspaper in teaching reading. The benefits attained the development of students’ reading ability, fun learning’s atmosphere and the increasing of students’ reading interest.